Hutang Uang Dibayar Emas dan Akibat Hukumnya Terhadap Para Pihak - Mahyuni, Mahyuni; Zulhamdi, Zulhamdi; Ulfah, Almira Keumala (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This study aims to analyze the payment of debt with gold and its legal consequences for the parties. The research method uses empirical juridical with a qualitative approach. This study was conducted in the Muslim community in North Aceh Regency. Data collection techniques use observation, interviews and documentation. The analysis technique uses an interactive model. The research findings were analyzed using the perspective of Islamic economic law. The results of the study indicate that the mechanism for paying debts with gold in North Aceh Regency, initially the debtor (muqtarid) receives money from the price/measurement of gold then returns it to the creditor (muqrid) with previously measured gold. Reviewed from Islamic economic law, paying debts with gold in North Aceh Regency violates the pillars of debt and receivables. In debt and receivable transactions,